Modelagem de corredores ótimos para linhas aéreas de transporte de energia elétrica - Pedro Bueno Rocha Campos (2014)
Demanded by the notorious need for economic growth of the productive sectors and infrastructure, the process of construction of new transportation lines of electric energy is rising in the Brazil. In Minas Gerais for example, Cemig Distribution Co, has invested more than R$ 3.3 billion in expansion of the electrical system between 2008and 2012 Projects in infrastructure for power transmission must follow regulations in order to satisfy criteria such as low cost and low environmental impact, which at first become conflicting. Therefore, the use of methods to foresee routes that optimize those criteria is extremely necessary. The Multicriteria Analysis associated with spatial modeling of landscape dynamics can provide the necessary elements for this goal. This study aims to optimize the transmission lines planning process by using landscape pattern analysis with include patterns extracted from existing infrastructure projects.The landscape pattern analysis is multitemporal, so the knowledge accumulated over the years of development infrastructure projects is absorbed in the model. A spatially explicit and dynamic model was developed. The model enables to study the spatial behavior of the process in order to set the location on the landscape of transmissionlines of energy. It also enables the combination of criteria for optimization of new projects using Multicriteria Analysis. The model employed robust methodologies, such as Weight of Evidence and Least Costly Path. The results demonstrate the efficiency of the method for identifying ideal places to locate the transmission lines. It provides comparative subsidies and alternatives that optimize the conflicting criteria. In addition,the method is effective to identify variables not considered in ordinary normativeregulations in the sector used to plan and built new power infrastructure projects.